Oral Rehabilitation of an Osteopetrosis Patient with Osteomyelitis - Tamer Celakil; Merve Dogan; Bilge Gokcen Rohlig; Gulumser Evlioglu; Haluk Keskin (Hindawi Limited, 2016)
Osteopetrosis is a congenital disorder characterized by increasing osteoclastic function resulting in osteomyelitis in the jaws. Orofacial findings in osteopetrosis patients are unerupted, malformed, or delayed teeth and many dental caries due to vulnerable enamel and dentin and osteomyelitis. Many reports have described that maxilla is an uncommon site of occurrence for osteomyelitis due to cortical bone morphology and collateral circulation. This report aims to discuss clinical features and prosthodontic management of a patient with clinical features of adult form of osteopetrosis and osteomyelitis in both jaws. The patient has reported better masticatory and speech efficiency with removable dentures in maxillary and mandibular jaw and also self-esteem improvement and family interaction.